KERAGAAN KONSUMSI IKAN DI INDONESIA TAHUN 2005—2011 - Yayuk Farida Baliwati; Yulmiaris Dwi Okto Putri (Food and Nutrition Society of Indonesia, 2012)
The objective of this study was to analyze fish consumption in Indonesia 2005— 2011. Data used in this study was based on the National Social and Economic Survey (SUSENAS). The study showed average national fish consumption 26.04 kg/capita/year, with average growth rate 0.05% per year. Fish consumption was higher in urban (26.51 kg/capita/year) than rural area (25.69kg/capita/year). Contribution of fresh fish and processed fish was higher in urban than rural area (63.0% and 14.0%). Processed food containing fish was higher in rural (8.30 kg/capita/year) than urban area (6.09 kg/capita/year). Low expenditure households consumed fish lower than the high expenditure. Recommendation of fish consumption is 32.70 kg/capita/year or 12.89 g protein/capita/day. The National fish requirement is projected 8.10 million tons at 2015.